2021
DOI: 10.3390/biom11121762
|View full text |Cite
|
Sign up to set email alerts
|

BXD Recombinant Inbred Mice as a Model to Study Neurotoxicity

Abstract: BXD recombinant inbred (RI) lines represent a genetic reference population derived from a cross between C57BL/6J mice (B6) and DBA/2J mice (D2), which through meiotic recombination events possesses recombinant chromosomes containing B6 or D2 haplotype segments. The quantitative trait loci (QTLs) are the locations of segregating genetic polymorphisms and are fundamental to understanding genetic diversity in human disease susceptibility and severity. QTL mapping represents the typical approach for identifying na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Studies using BXD recombinant inbred (RI) mice investigated genes that are associated with alcohol sensitivity and a predisposition to alcoholism to understand the underlying mechanisms of neurotoxicity in response to ethanol [ 79 ]. In evaluations of the genetic susceptibility to ethanol consumption and withdrawal, strains showed contrasting behavioral responses to ethanol, since the BXD RI strains showed that C57BL/6J (B6) inbred mice were able to drink large amounts of ethanol voluntarily, while DBA/2J (D2) mice showed improved withdrawal to acute ethanol [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies using BXD recombinant inbred (RI) mice investigated genes that are associated with alcohol sensitivity and a predisposition to alcoholism to understand the underlying mechanisms of neurotoxicity in response to ethanol [ 79 ]. In evaluations of the genetic susceptibility to ethanol consumption and withdrawal, strains showed contrasting behavioral responses to ethanol, since the BXD RI strains showed that C57BL/6J (B6) inbred mice were able to drink large amounts of ethanol voluntarily, while DBA/2J (D2) mice showed improved withdrawal to acute ethanol [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, major questions persist about the association of cardiac Cu concentrations with heart morphology and function and its underlying genetic regulation. To this end, we have previously applied a systems genetics approach using the BXD family of RI mice, a murine GRP that has previously been successfully used for several QTL analyses to identify candidate genes and gene networks that underlie the effects of trace metals in the brain ( 34 , 35 ). Similarly, in the current study, we showed that the cardiac Cu concentration in BXD mice is significantly correlated with various echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…(3) a strain often crossed with C57BL/6J that is used for studying genotype-phenotype interactions (Geisert and Williams, 2020;Martins et al, 2021;Sasani et al, 2022); and (4) numerous other models which contain unique phenotypes due to genetic background, such as the PWD/PhJ strain, a mouse historically utilized to model hybrid sterility (Chubb and Nolan, 1987;Lustyk et al, 2019). The resulting SV calls can be used for identifying variants associated with disease and to study large segments of DNA which were hidden from previous genomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…We characterized and sequence-resolved genome wide SVs present in 20 laboratory mouse strains with longread sequencing technology. This cohort represents various popular research models such as: (1) the parental founders of the CC and DO crosses, which are powerful selective breeding panels used for trait mapping (Iraqi et al, 2008); (2) six resultant CC strains which have interesting phenotypes; (3) a strain often crossed with C57BL/6J that is used for studying genotype-phenotype interactions (Geisert and Williams, 2020; Martins et al, 2021; Sasani et al ., 2022); and (4) numerous other models which contain unique phenotypes due to genetic background, such as the PWD/PhJ strain, a mouse historically utilized to model hybrid sterility (Chubb and Nolan, 1987; Lustyk et al, 2019). The resulting SV calls can be used for identifying variants associated with disease and to study large segments of DNA which were hidden from previous genomic studies.…”
Section: Discussionmentioning
confidence: 99%